2019
DOI: 10.2147/ott.s200754
|View full text |Cite
|
Sign up to set email alerts
|

<p>Modified FOLFIRINOX for unresectable locally advanced/metastatic pancreatic cancer. A real-world comparison of an attenuated with a full dose in a single center experience</p>

Abstract: Purpose: Metastatic pancreatic adenocarcinoma has a very poor prognosis. Although irinotecan, oxaliplatin and leucovorin-modulated fluorouracil (FOLFIRINOX) significantly increases survival in advanced pancreatic cancer, compared to employing only gemcitabine (GEM), toxicities have tempered enthusiasm for its use. Methods: This study retrospectively analyses the real-world clinical practice with full and attenuated doses of FOLFIRINOX in unselected patients with locally advan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…In another aspect of tolerability, dose modification was more frequently in FFX group. The efficacy and tolerability of FFX with modified dose for unresectable PC demonstrated in several studies [ 20 , 21 ]. Modified FFX showed comparable survival outcomes compared to full dose regimen and less adverse events [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another aspect of tolerability, dose modification was more frequently in FFX group. The efficacy and tolerability of FFX with modified dose for unresectable PC demonstrated in several studies [ 20 , 21 ]. Modified FFX showed comparable survival outcomes compared to full dose regimen and less adverse events [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy and tolerability of FFX with modified dose for unresectable PC demonstrated in several studies [ 20 , 21 ]. Modified FFX showed comparable survival outcomes compared to full dose regimen and less adverse events [ 20 ]. Appropriate dose modification and tolerance to chemotherapy would provide patients with more chances for second-line treatment, and more patients in the FFX group received second-line chemotherapy in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the use of the mFFN scheme, Khushman and colleagues [40] demonstrated that the dose intensity and duration were associated with increased survival, arguing against dose attenuated versions of this regimen. Opposite to this study, several studies recently demonstrated that the reduced doses of the FFN scheme did not have an impact on the survival [41,42].…”
Section: Resultsmentioning
confidence: 88%
“…Finally, 37 studies were included for evidencemapping of the trend of 'planned' and 'actual' dose of FOLFIRINOX, and 27 studies were included in the meta-analysis for comparison of clinical outcome according to planned dose of FOLFIRINOX. 3,[6][7][8] Description of the included studies Of the 37 studies, 11 and 26 were prospective studies 3,[16][17][18][19][20][21][22][23][24][25] and retrospective studies, [6][7][8] respectively (Table 1). The country included the most was Japan (N = 10) followed by Korea (N = 6), USA (N = 5), and China (N = 5).…”
Section: Resultsmentioning
confidence: 99%